Capacity Building for Gender-Responsive Street Vendors Through Training in Digital Financial Literacy and Micro Enterprise Management - Hapsari, Yustia; Prasetyo, Irwan; Herwinarni, Yuniarti (Universitas Pancasakti Tegal, 2025)
This community service activity aims to improve the capacity of street vendors under the guidance of TBM PKBM Sakila Kerti at Tegal Type A Terminal through gender‑responsive digital financial literacy training and micro‑business management. The background of this activity is the low understanding of street vendors regarding systematic financial management, limited ability to use digital financial services, and the remaining gender gap in access and business decision‑making. The implementation method uses a participatory approach that actively involves vendors at every stage, from needs identification, training implementation, to evaluation and monitoring. The training was carried out in several sessions covering an introduction and practical use of digital finance (QRIS), simple bookkeeping, capital management, and micro‑business development strategies. All sessions were combined with a gender‑responsive approach to ensure equal involvement of both male and female vendors in understanding and applying the material. Evaluation was conducted through pre‑tests and post‑tests, observations, and group discussions to measure improvements in participants’ understanding and skills. The results show significant improvements in digital financial literacy, simple financial recording skills, and micro‑business management abilities among street vendors. In addition, the training successfully encouraged awareness of the importance of gender equality in managing family businesses, where female vendors gained a greater role in financial decision‑making. This activity supports more equitable and sustainable economic empowerment while improving business capability.